How Can Pharmacists Support STI Prevention and Treatment Among Female Adolescents and Young Adults? - Olufunmilola Abraham; Amanda Brothers; Mara Rubin; Richelle DeBlasio (University of Minnesota Libraries Publishing, 2017)
Sexual and reproductive health is a critical focus area for adolescents and young adults (AYAs). Of the 20 million newly diagnosed Sexually Transmitted Infections (STIs) annually, nearly half of them are contracted by young people between the ages of 15 to 24. It has become increasingly necessary to improve awareness and prevention of STIs during adolescent years. The knowledge gained through appropriately relevant sexual and reproductive health education may persist as adolescents transition into adulthood. Community pharmacists interact with AYAs frequently and are therefore well positioned to engage this vulnerable population in conversations about their sexual and reproductive health through use innovative and interactive technologies. For instance, mobile applications are easily accessible to AYAs and can allow pharmacists to disseminate relevant medication information to smartphone users that download adolescent-tailored mobile applications. Although many medication adherence apps are currently available on the market, none of these apps are tailored towards sexual reproductive health information for female AYAs. A mobile-based program designed to provide a pharmacist-guided sexual and reproductive health education to female AYAs may help to address the lapses in current adolescent-aged school health classes. In the future, usage of this intervention would improve the accuracy and comprehension of female adolescents and young adults' awareness and knowledge of their sexual and reproductive health. As a result, further research should be conducted to develop mobile applications conducive to adolescent and young adults to address sexual and reproductive health issues. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties.   Type: Idea Paper